Photocatalytic Degradation of Acidic Blue Black 10B Using SrFe0.5Co0.5O3-d - Meng1, Hongyan; Qiao2, Jun; Huang1, Xianghong (Asian Journal of Chemistry, 2014)
The perovskite-type oxides SrFe0.5Co0.5O3-d is prepared by citrate method using strontium nitrate, iron nitrate, cobalt nitrate as raw materials. The structure of SrFe0.5Co0.5O3-d is characterized by X-ray diffraction, scanning electron microscopy (SEM), Brunner-Emmet-Teller (BET) measurements. The photocatalytic properties of perovskite oxides SrFe0.5Co0.5O3-d were evaluated by photocatalytic degradation of acid blue black 10B under the irradiation of UV. Several operational parameters effecting the photocatalytic degradation of acidic blue black 10B (AB) was studied systematically, including irradiation time, photocatalyst dose, acidic blue black 10B initial concentration and amount of H2O2 (1 %). The results showed that perovskite-type oxides SrFe0.5Co0.5O3-d exhibited excellent photocatalytic properties and the degradation of acidic blue black 10B followed the pseudo-first-order kinetics.